Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interpellations: Three Essays on Kent Monkman - Thériault, Michèle (Galerie Leonard & Bina Ellen art gallery, 2012)
Trois essais de Richard W. Hill, Jonathan D Katz et Todd B Porterfield.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

“Tu vida también es mi país”: sexualidades disonantes y fugas de género en Liliana Felipe y Jesusa Rodríguez - Muelle, Camila Esguerra; Martínez, Alejandra Quintana (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2018)
Este artículo propone una reflexión sobre las prácticas vitales, artísticas y políticas de Liliana Felipe y Jesusa Rodríguez y sus experiencias de desobediencia frente a los regímenes de sexualidad y género articulados a regímenes de terror en México y Argentina. La metodología usada para llegar a la reflexión fue un análisis crítico multimodal del discurso hecho desde una perspectiva interseccional y descolonial que supone el análisis tanto de contextos como de los textos, subtextos y texturas que componen la obra y vida de estas artistas. Desde esta postura epistemológica, la obra performática y musical de Liliana y Jesusa es vista como un acervo de discursos multimodales. Nuestra reflexión muestra cómo la creación, la experiencia —entendida como lugar político— y las propuestas colectivas de Liliana y Jesusa se ponen en juego en un campo de lucha performativa donde sus discursos desobedientes proponen maneras de resistencia y fuga a los regímenes coloniales-modernos- capitalistas de género y sexualidad. Jesusa y Liliana proponen una obra multimodal y multimedial que fisura los límites de los géneros discursivos, los géneros musicales, el género gramatical y el sistema sexo género, lo cual amerita una mirada indisciplinada. Este artículo resulta ser un abordaje novedoso en la medida en que se acerca a la experiencia y a la obra de estas dos mujeres, no desde una visión disciplinar, sino a partir de una mirada transdisciplinaria, interseccional y descolonial que asume la producción artística como una apuesta política donde los límites entre lo personal y lo público se borran. This article seeks to do a reflection both on the vital, artistic and political practices of Liliana Felipe and Jesusa Rodríguez and on their experiences of disobedience to the regimes of sexuality and gender, which are articulated to regimes of terror in Mexico and Argentina. The methodology used in order to make this reflection was a Multimodal Critical Discourse Analysis from both an intersectional and decolonial perspective. This methodology implies the analysis of contexts, texts, subtexts and textures that make up the work and life of these artists. From this epistemological position, the performative and musical work of Liliana and Jesusa is seen as a collection of multimodal discourses. Creation, experience —understood as a political locus— and the collective proposals of Liliana and Jesusa are put into play in a field of performative struggle where their disobedient discourses propose ways of resistance to colonial-modern-capitalist regimes of gender and sexuality.Jesusa and Liliana propose a multimodal and multimedial work that fissures the limits of the discursive genres, the musical genres, the grammatical gender and the gender sex system, which deserves an undisciplined look. This article proposes an original approach insofar as it approaches the experience and work of these two women not from a disciplinary view, but from a transdisciplinary, intersectional and decolonial point of view, that assumes artistic production as a political commitment in where the boundaries between the personal and the public are erased.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé